2016
DOI: 10.1016/j.jams.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Response to Manual Acupuncture Needle Stimulation among Apparently Healthy Nigerian Adults

Abstract: This study investigated experience with acupuncture needle stimulation of apparently healthy adult Nigerians and the responses of the systolic blood pressure (SBP), diastolic blood pressure, heart rate (HR), and rate pressure products (RPP) to acupuncture at both real acupuncture points relevant to the treatment of cardiovascular disorder and sham acupuncture points not relevant to the treatment of cardiovascular disorder. Seventy-eight participants were randomly placed into three groups: the real acupuncture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The animal study and clinical trial has demonstrated that sham acupuncture treatment (acupuncture on the nonacupoints) could not lower BP [107, 108]. When irrelevant acupoints (e.g., LI6, LI7, GB37, GB38, and GB39) were selected, the antihypertensive effect is not achieved too [15].…”
Section: Discussionmentioning
confidence: 99%
“…The animal study and clinical trial has demonstrated that sham acupuncture treatment (acupuncture on the nonacupoints) could not lower BP [107, 108]. When irrelevant acupoints (e.g., LI6, LI7, GB37, GB38, and GB39) were selected, the antihypertensive effect is not achieved too [15].…”
Section: Discussionmentioning
confidence: 99%